Mineralogy of pancreatic calculi - Liberto de Pablo-Galán; María D. Lastra-Azpilicueta (Revista Mexicana de Ciencias Geológicas)
Pancreatic calculi from patients with chronic pancreatic disorders from the Mexico City area are 75% calcitic stones, with an average weight of 1.30 g and ranging in size from 7 to 28 mm, and 25% organic stones, with an average weight of 0.11 g and ranging in size from 4 to 12 mm… in order to continue, download the full paper in PDF.